Load balancing algorithms with cluster in cloud environment. (25th August 2022) - Kshama, S.B.; Shobha, K.R.
Load balancing is one of the important aspects of cloud computing. Its main goal is to improve system performance and to reduce its cost. Cloud computing has a dedicated load balancer to attain this. Sometimes, heavy traffic may overwhelm the load balancer and disrupt it to achieve its goal. The repeated disruption has an impact on customer service and results in poor performance. The clustering technique gives a solution to this by reducing the burden on a single machine and improves system performance. In this paper, an analysis has been made to test the performance of the load balancer with and without the cluster. The previously proposed capacity-based load balancing (CBLB) and artificial bee colony_CBLB algorithms are considered during this experiment. The results are compared by applying clusters on existing load balancing algorithms. In addition to this, the performance of the ABC_CBLB with cluster is also compared with two existing cluster load balancing algorithms. The results of CBLB and ABC with cluster are better than the other comparing algorithms.